О рыцарях и лжецах: роман / Татьяна Веденская - Веденская Татьяна Евгеньевна (Жизнь прекрасна, 2018)
Экземпляры: (20180713) / Инвентарный номер: 40662 / Цена: 270.83 / Сис.шифр: Р2 / Авт.знак: В 26 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6